Synthesis of thermoplastic starch-bacterial cellulose nanocomposites via in situ fermentation - Osorio, Marlon A. (2014)
In this paper, a nanocomposite based on thermoplastic starch (TPS) reinforced with bacterial cellulose (BC) nanoribbons was synthesized by in situ fermentation and chemical crosslinking. BC nanoribbons were produced by a Colombian native strain of Gluconacetobacter medellinensis; the nanocomposite was plasticized with glycerol and crosslinked with citric acid. The reinforcement percentage in the nanocomposites remained constant throughout the fermentation time because of the TPS absorption capability of the BC network. Nanocomposites produced after fermentation for seven days were characterized using thermogravimetric analysis (TGA); Fourier transformed infrared spectroscopy with attenuated total reflectance (FTIR-ATR), mechanical testing and scanning electron microscopy (SEM). The new TPS/BC nanocomposites exhibit strong interfacial adhesion, improved thermal behavior, water stability and enhanced mechanical properties. These findings support the applications of starch in the packaging industry.